Research progress of nanocarriers for gene therapy targeting abnormal glucose and lipid metabolism in tumors. (1st January 2021) - Zeng, Xianhu; Li, Zhipeng; Zhu, Chunrong; Xu, Lisa; Sun, Yong; Han, Shangcong
Abstract: In recent years, the incidence of various types of tumors has gradually increased, and it has also been found that there is a certain correlation between abnormal glucose and lipid metabolism and tumors. Glycolipid metabolism can promote tumor progression through multiple pathways, and the expression of related genes also directly or indirectly affects tumor metabolism, metastasis, invasion, and apoptosis. There has been much research on targeted drug delivery systems designed for abnormal glucose and lipid metabolism due to their accuracy and efficiency when used for tumor therapy. In addition, gene mutations have become an important factor in tumorigenesis. For this reason, gene therapy consisting of drugs designed for certain specifically expressed genes have been transfected into target cells to express or silence the corresponding proteins. Targeted gene drug vectors that achieve their corresponding therapeutic purposes are also rapidly developing. The genes related to glucose and lipid metabolism are considered as the target, and a corresponding gene drug carrier is constructed to influence and interfere with the expression of related genes, so as to block the tumorigenesis process and inhibit tumor growth. Designing drugs that target genes related to glucose and lipid metabolism within tumors is considered to be a promising strategy for the treatment of tumor diseases. This article summarizes the chemical drugs/gene drug delivery systems and the corresponding methods used in recent years for the treatment of abnormal glucose and lipid metabolism of tumors, and provides a theoretical basis for the development of glucolipid metabolism related therapeutic methods. Graphical Abstract: UF0001